Development of a Smart Home Control System Based on the Internet of Things Using an Android Application - Ayu Ramadhana; Yulkifli; Mairizwan (Research on Instrumentation, 2025)
Housing is a fundamental human necessity that serves as a place for living, resting, and ensuring comfort and security. However, inefficient electricity consumption and inadequate security systems remain prevalent challenges in residential environments. This study aims to design and evaluate the performance of an Internet of Things-based smart home control system integrated with an Android application. The research adopts an engineering methodology consisting of system design, development, and experimental testing. The proposed system utilizes an ESP32 microcontroller, Passive Infrared sensor, Light Dependent Resistor sensor, and relay module, with an Android-based interface developed using MIT App Inventor and supported by Firebase for real-time data communication. The system has two modes: automated mode, which is powered by sensor inputs, and manual application mode, which is enabled by voice instructions. In automatic mode, lights are engaged when low ambient light and movements are detected, whereas in application mode, users can control illumination remotely via voice interaction. Experimental results show that the system achieves 100% accuracy and precision under the test conditions. These findings show that the suggested smart home system is extremely dependable and successful in optimising energy use and improving residential security.